1943
DOI: 10.1037/h0061753
|View full text |Cite
|
Sign up to set email alerts
|

Likes, dislikes, and vocational interests.

Abstract: Vocational interests, as defined by the Strong Vocational Interest Blank, are, for the most part, expressions of liking and disliking. Attention has hitherto been focused upon the objects of this liking and disliking. The interdependency between these objects cannot be denied. Thorndike, ( 9) after an extensive study on the interests of adults, concluded, "All these records go to show two general facts. First, there is great specialization of interests Second, such group factors as appear seem more related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1958
1958
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…Darcy and Tracey argued that this pattern of responding was not error but had substantive meaning. Those individuals who have low average scores across all scales have been found to be cynical and cautious while those with high average scores are cheerful and enthusiastic (Berdie, 1943;Holland, 1997;Stewart, 1960). Darcy and Tracey (2003) posit that the mean interest level is indicative of the construct of interest flexibility.…”
Section: Individual Difference Moderationmentioning
confidence: 97%
“…Darcy and Tracey argued that this pattern of responding was not error but had substantive meaning. Those individuals who have low average scores across all scales have been found to be cynical and cautious while those with high average scores are cheerful and enthusiastic (Berdie, 1943;Holland, 1997;Stewart, 1960). Darcy and Tracey (2003) posit that the mean interest level is indicative of the construct of interest flexibility.…”
Section: Individual Difference Moderationmentioning
confidence: 97%
“…To the extent this was the case in either of our inventories, the factors were again undesirable for our purposes. Without disagreeing that acquiescence may be involved, several investigators (Berdie, 1943;Holland, 1985;Stewart, 1960) suggested that the general factor may represent some aspect of personality style or ability perception that has substantive meaning. These researchers noted that people who express a wide range of interests tend to be enthusiastic, dominant, sociable, impulsive, and cheerful, whereas those who express few interests tend to be cautious, cynical, depressive, and moody.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Other researchers (e.g., Berdie, 1943;Holland, 1985;Stewart, 1960), although not necessarily disagreeing with the effect of acquiescence on the validity of interest scores, viewed the tendency to respond like or dislike as an indicator of personality style and thus regarded it as having substantive meaning. Those who endorse a high number of items tend to be characterized as enthusiastic, dominant, sociable, impulsive, and cheerful, whereas those who dislike a high number of items tend to be characterized as cautious, cynical, depressive, and moody (Berdie, 1943;Holland, 1997;Stewart, 1960). If there were substantive meaning to the general factor, its removal could result in attenuated relations and thus decrease validity, similar to what occurs in personality assessment.…”
Section: General Response Factor In Vocational Interest Assessmentmentioning
confidence: 99%